Role of inositol phospholipid signaling in natural killer cell biology - Gumbleton, Matthew; Kerr, William G. (Frontiers in Immunology, 2013)
Natural killer (NK) cells are important for host defense against malignancy and infection. At a cellular level NK cells are activated when signals from activating receptors exceed signaling from inhibitory receptors. At a molecular level NK cells undergo an education process to both prevent autoimmunity and acquire lytic capacity. Mouse models have shown important roles for inositol phospholipid signaling in lymphocytes. NK cells from mice with deletion in different members of the inositol phospholipid signaling pathway exhibit defects in development, NK cell repertoire expression and effector function. Here we review the current state of knowledge concerning the function of inositol phospholipid signaling components in NK cell biology.